2010
DOI: 10.1186/1477-7827-8-82
|View full text |Cite
|
Sign up to set email alerts
|

Collagen concentration and biomechanical properties of samples from the lower uterine cervix in relation to age and parity in non-pregnant women

Abstract: BackgroundDuring normal pregnancy the cervix has a load bearing function. The cervical tissue consists mainly of an extracellular matrix (ECM) rich in collagen; important for the biomechanical properties. The aim of the present study was to evaluate how the biomechanical strength of samples from the distal cervix is associated with collagen content in relation to age and parity. This study demonstrates a method to investigate cervical tissue from women who still have their uterus in situ.MethodsCervical punch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…Age is known to affect the mechanical properties of nonpregnant cervical tissue. Spherical indentation tests reveal that older samples have a lower force response to compressive indentation (Yao et al, 2014), while in another study the uni-axial tensile response to loading for older tissue is higher (Oxlund et al, 2010b). Age is an important factor because most ex vivo studies have been conducted on hysterectomy specimens, and the age of the hysterectomy patient is often older than that of a typical pregnant patient.…”
Section: Cervical Tissue Mechanical Propertiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Age is known to affect the mechanical properties of nonpregnant cervical tissue. Spherical indentation tests reveal that older samples have a lower force response to compressive indentation (Yao et al, 2014), while in another study the uni-axial tensile response to loading for older tissue is higher (Oxlund et al, 2010b). Age is an important factor because most ex vivo studies have been conducted on hysterectomy specimens, and the age of the hysterectomy patient is often older than that of a typical pregnant patient.…”
Section: Cervical Tissue Mechanical Propertiesmentioning
confidence: 93%
“…Insight into the physiologic loads experienced during pregnancy and the load-carrying capability of the cervix have been derived from finite element models (Fernandez et al, 2015; House et al, 2012, 2013; Mahmoud et al, 2013; Paskaleva, 2007), mechanical and biochemical studies of ex vivo tissue specimens (Conrad et al, 1980; Conrad and Ueland, 1976, 1979; Fernandez et al, 2013; Gan et al, 2014; Myers et al, 2008, 2010; Oxlund et al, 2010a,b; Petersen et al, 1991; Rechberger et al, 1988; Yao et al, 2014), in vivo mechanical and biochemical interrogations of the cervix (Badir et al, 2013a; Bauer et al, 2007; Feltovich et al, 2010, 2012; Feltovich and Hall, 2013; Hee et al, 2014; House et al, 2005, 2009; Hricak et al, 1990; Maldjian et al, 1999; Mazza et al, 2006, 2013; Parra-Saavedra et al, 2011), and theoretical mechanics (Liao et al, 2014; Myers and Ateshian, 2014; Paskaleva, 2007). At the present time, there is no single set of correlating geometric and material property data from a single pregnant patient throughout gestation.…”
Section: The Multi-scale Mechanical Environment Of Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Magnuson and colleagues noted that fibronectin, a key component of ECM, undergoes changes in alternative splicing with aging both in vitro and in vivo, but that these changes are tissue specific. 73 Furthermore, it has been reported that the collagen content of human tissue increases with age in the left ventricle (LV) and uterine cervix, 74 but decreases in spinal discs. 75 Consequently, we divide our review of age-associated compositional modifications to the ECM by tissue type.…”
Section: Compositional Changes With Age and Potential Influence On Msmentioning
confidence: 99%
“…However, conventional ultrasound imaging cannot reliably differentiate myometrial abnormalities such as adenomyosis and leiomyomas, or endometrial abnormalities such as hyperplasia, polyps, and cancer (21, 25). Measurement of the stiffness (2629) and acoustic (30–35) properties of the cervix and uterus and associated pathologies may provide important insights on ability to differentiate between tissue types.…”
Section: Introductionmentioning
confidence: 99%